Prevalence of menopausal symptoms and its association with various factors among women in post menopausal age group: a cross-sectional study - Satapathy, Sushree Priyadarsini; Karmee, Nivedita; Dash, Rabinarayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menopause is an important time in women's life and it is a natural event in the process of aging. The onset of menopause heralds a time of diminished estrogen exposure, which may have both acute and chronic effect on health and quality of life. Methods: It was a cross sectional study, conducted for a period of 3months i.e. June to August 2018 among post menopausal women in 8 selected villages with a sample size of 247. Results: The common post- menopausal symptoms were joint and muscular discomfort, bladder problems, symptoms of dryness of vagina, physical and mental exhaustion. Factors like education, occupation, socio-economic status, marital status, parity, mode of delivery, age at menopause and BMI was related to one or more menopausal symptoms. Conclusions: Proper and timely intervention among post menopausal women will help to reduce the symptoms and lead a better quality of life.